PEMAHAMAN KARYAWAN BTM AT-TAQWA TERHADAP TARJIH MUHAMMADIYAH ASPEK IBADAH - Syamsurizal, Syamsurizal; Rosdialena, Rosdialena; Marlius, Yoni (Menara Ilmu, 2021)
This study aims to reveal how the understanding of BTM at-Taqwa employees to the results of muhammadiyah tarjih verdicts, especially in the aspect of worship, is important to do considering all human resources working in muhammadiyah business charities are required to practice Islamic teachings, especially those in accordance with the decision of muhammadiyah tarjih results. The research was conducted at BTM at-Taqwa Muhammadiyah Padang City, the approach used is qualitative, data collection techniques using observation, interview and documentation. The results of this study prove that btm at-Taqwa Muhammadiyah employees do not have a strong understanding of the verdict of Tarjih Muhammadiyah, especially in the aspect of worship, this conclusion is based on the low practice of BTM at-Taqwa employees to pray in accordance with the results of tarjih verdicts. The cause of the low understanding of employees to the understanding of tarjih is due to the lack of coaching in the form of studies, no regulations that support in writing, the absence of leadership control, and the absence of cadre training such as baitul Arqam, and Darul Arqam.